Las máximas conversacionales desde un enfoque cognitivo - Trenc, Andreja (Verba hispanica, 2014)
The latest investigations in the field of psycholinguistics and sociolinguistics advocate principles of efficient communication in accordance with ethical, logical and psychological dimensions of language use. As a consequence, new theories of interpersonal verbal transactions as a part of cognitive activity (Lee, Nowak y Pinker, 2008; Pinker y Lee, 2010) or politeness theory aimed at the speakers who are negotiating the best linguistic options in order to achieve the desired social purpose (Brown, Levinson, 1987), consider communication as fulfillment of principles of cooperation. The purpose of the paper is to propose alternative criteria for the discourse analysis of phenomena from indirect speech to the present socio-pragmatic cooperative principle (Grice, 1975). The criteria follow psycholinguistic and strategic parameters, such as deniability and cancelability, which are negotiated during an indirect speech act and can be applied to the speech act at the speaker%s decision. The paper presents an application of the cancelability parameter to examples of %off-record% indirect speech in Spanish and also refers to some significant data from a research on English Language in order to advocate a psycholinguistic model as a framework which can be used in order to define the "off-record" indirect speech with more reliability and precision.
Keywords: sociolinguistics; sociolingvistika; sporazumevanje; govorna interakcija; konverzacijske implikature; konverzacijske maksime; indirektni govor; španščina; Spanish